Pengembangan LKS Berbasis Contextual Teaching and Learning Materi Hama dan Penyakit Tumbuhan - ZULIS SHOIDAH (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2012)
Abstract—Student Worksheet based on contextual teaching and learning (CTL) on the material in the Plant Pests and Diseases for the junior class VIII. has developed. The purposes of this study are describe the feasibility of Student Worksheet doing learning, readability and student responses. The research is conducted based on 4D models. Student Worksheet was tested on 15 students in grade VIII Paciran SMPN 1. The results revelaed that the Student Worksheet is feasible, obtain good students’ response, readable, and doing learning also good. Keywords: Student worksheet (LKS), Contextual Teaching and Learning (CTL), Pest and Plants Diseases.